Pengembangan Desa Wisata Taman Tangkilan Berbasis Teknologi Dengan Memberdayakan Generasi Muda Pada Desa Sidoarum Godean Kabupaten Sleman - Nurul Kurniawati; Riandhita Eri Werdani; Kholidin Kholidin (Yayasan Sumber Daya Manusia Cerdas, 2023)
The development of tourist villages is made one of the efforts to empower village communities through tourism activities, so that they can provide results in improving the economic conditions of the community. Therefore, this development effort should be carried out with the principles of empowerment and community-based tourism. The role of the community, especially the younger generation, is needed as the main actors in all stages of planning, implementing, monitoring and evaluating activities. The method of implementing community service includes a description of the problem of environmental conditions and the selection of solutions that will be applied to solve priority problems in society. The form of activity chosen in this service is through program socialization and counseling to increase digital literacy in supporting tourism development. The development of the Taman Tangkilan tourism village by the government of Sidoarum Godean Village, Sleman Regency can be seen that it has not been implemented optimally, this is evidenced by the lack of village government in providing support and promoting the Tangkilan Park in Sidoarum Godean Village.